T lymphocytes synthesize and export heparin-binding epidermal growth factor-like growth factor and basic fibroblast growth factor, mitogens for vascular cells and fibroblasts: differential production and release by CD4+ and CD8+ T cells. - Blotnick, S (1994)
T lymphocytes infiltrate wounds, tumors, and atherosclerotic plaques, pathophysiological processes characterized by the migration and proliferation of vascular cells and fibroblasts. Although T lymphocytes are known to produce cytokines for inflammatory cells, it has not been demonstrated that they synthesize growth factors that are mitogenic for vascular cells and fibroblasts. We demonstrate that cultured T lymphocytes isolated from normal human peripheral blood synthesize and export two well-characterized growth factors, heparin-binding epidermal growth factor-like growth factor (HB-EGF) and basic fibroblast growth factor (bFGF). This conclusion is based on mRNA expression analysis, heparin-affinity chromatography profiles, target-cell specificity, and functional inhibition by specific neutralizing antibodies. Atypically, a substantial amount of T-cell-derived bFGF-like activity appears to be constitutively released into conditioned medium, almost as much as is associated with T-cell lysates. bFGF is synthesized and exported by purified CD4+ and CD8+ T cells, whereas HB-EGF is synthesized and exported primarily by CD4+ T cells. The T-cell-derived HB-EGF and bFGF activities are potent mitogens for fibroblasts and smooth muscle cells, and the bFGF-like activity is also mitogenic for endothelial cells. These results suggest that T lymphocytes may play key roles in mediating smooth muscle hyperplasia associated with atherosclerosis and in angiogenesis associated with wound healing and tumor growth by acting locally to deliver vascular-cell growth factors to tissues.